Improving Sensemaking in Social Work: A worked example with Deleuze and Art. (September 2021) - Robson, Ian
Social Work is all about Sensemaking, but Sensemaking, as we currently know it, is not fit for purpose in Social Work. Developed by Karl E.Weick, Sensemaking describes the process of coming to understand and act in circumstances that are confusing or otherwise problematic. In this article, the author provides a creative and inventive response to the limitations of Sensemaking in Social Work through the philosophy of Gilles Deleuze, and the use of artistic practices. In this article, he presents two stories; firstly, a story about overcoming 'stuckness' in a study of English Children's Centre practitioners, and secondly, a bigger story about the limitations of Sensemaking in Social Work. These two stories are connected by Deleuze, and Art. The author responds to the opportunities presented by Deleuze by creating a series of visual Motifs, which act as idea-objects, used in his Sensemaking. He argues that whilst Social Workers do not need to be artists to make better sense of situations, they can use their own Motifs to better consider materiality, sense and affect in situations.